Kurikulum Madrasah: Studi Perbandingan Madrasah di Asia - Nasir, Muhammad (Nadwa: Jurnal Pendidikan Islam, 2015)
Madrasah is one of the oldest Islamic education institution. At first, the school only develop curriculum with Islamic competences are the main objectives .. Madrasah today has been integrating the Islamic knowledge and sciences. Several countries in Asia both predominantly Muslim and minority seems that they have developed madrasa education institutions as one attractive option for people. Every country has the madrassa who coined according to the characteristics typi-cal of a country, There are significant similarities, all madrassas in various countries have a curriculum that combines religious education in the form of Aquran, Hadith, Fiqh, Tawhid, historical and moral theology and general edu-cation based on demands of each countryÂ AbstrakMadrasah merupakan salah lembaga pendidikan Islam tertua. Pada mulanya, ma-drasah hanya mengembangan kurikulum dengan kompetensi keislaman yang menjadi tujuan utama. Madrasah masa kini telah memadukan antara ilmu-ilmu kesilaman, ilmu-ilmu umum dan teknoogi. Beberapa negara di Asia baik yang penduduknya mayoritas muslim maupun yang minoritas telah memgembangkan lembaga pendidikan madrasah sebagai salah satu pilihan menarik buat masyara-katnya. Setiap negara memiliki madrasah yang memiiki ciri khas sesuai dengan karakteristik negara di mana madrasah itu berada, Terdapat persamaan yang penting, semua madrasah di berbagai negara memiliki kurikulum yang mema-dukan antara pendidikan keagamaan berupa Aquran, Hadis, Fiqh, Tauhid, sejarah dan akidah akhlak dan pendidian umum yang menjadi tuntutan negara masing-masing